Investment and Sustainable Economic Growth: Empirical Perspective on Kuwait's Dual Challenge During the COVID-19 Pandemic and Beyond - Al-Jabsheh, Faten; Al-Qudsi, Sulayman; Hajeeh, Mohammed A. (International Journal of Economics and Financial Issues, 2021)
Endogenous economic growth theories have pointed to private investment as one of the determinants of long run, sustainable economic growth; a well-studied relationship in the development economics literature, both theoretically and empirically. One of the main reasons the Kuwaiti economy has not achieved its aspired degree of economic diversification over decades, is the relatively low level of private investment, which has eventuated in a relatively small private sector, partly due to an unimproved investment ecosystem. Like other economies, investment in Kuwait is a robust growth driver especially as a policy tool to achieve a digital, knowledge-based economy that leapfrogs on innovative technological investments, as ambitiously strategized by the Kuwait Vision 2035. The eruption of the coronavirus pandemic and the deep recession it triggered is likely to become a major hurdle in the way of spurring sufficient quality investments. With contracted GDP and collapsed oil prices, export and fiscal revenues shrink substantially, reducing investment activity and hence negatively affecting investment. This paper focuses on the role of private investment as a function of sustainable economic growth. Specifically, this paper aims to delineate the relationship between investment and economic growth in Kuwait by outlining; the determinants and impediments of investment, investment trends and behavior, innovative models of investment in Kuwait and applying a set of seven simulation-based scenarios of investment modelled as autoregressive distributed lags. By so doing, the paper elucidates the impact of critical variables including; non-oil GDP growth, interest rates management, attracting and fostering FDI inflows, as well as the recession plagued fiscal and trade balances, in order to estimate the magnitude and time-path of key policy variables on investment. The findings illustrate the rigidity of investment when recession drags GDP, FDI, exports and trade balances as well as fiscal revenues. Keywords: Oil Surplus Economy, Kuwait Vision 2035, Diversification, Coronavirus, Simulation, Autoregressive Lag Mode JEL Classifications: C1, C15, F, F01 DOI: https://doi.org/10.32479/ijefi.11513